International perspectives on child abuse and children's testimony : psychological research and law - Bottoms, Bette L. (SAGE Publications, 1996)
Child witnesses pose unique challenges to the legal system, and courtrooms are daunting and alien to children. Timely and truly international in scope, this volume focuses on the techniques and procedures used to accommodate child witnesses in legal systems -- and on research investigating the effectiveness and implications of those techniques -- around the world: England, Scotland, The Netherlands, Israel, South Africa, Hong Kong, Australia, Canada, New Zealand, the United States and India.